Zoonosis and the law: a case study of legal game meat regulation and control in Zambia - Mukanganwa, Batsirai Alexander; Sukmawati, Farah Aisyah; Erasmus, Sara Wilhelmina (Frontiers in Conservation Science, 2025)
Globally, game meat production is increasing. Yet, in many countries, game meat supply chains are not formally regulated and traceability issues have also been raised. As a consequence, there is an increased risk of zoonotic disease outbreaks. Thus, there is a growing call for a greater role of law and policy (environmental justice) in game animal and game meat products to secure animal and human health. Zambia is one of the countries where game meat production is increasing and legally traded. There is a paucity of information on Zambian laws, regulations, and policies governing the game meat trade. To understand this phenomenon in light of environmental justice concerns, we conducted a case study analyzing the Zambian regulatory framework and policies related to the game meat supply chain. The study included a review of Zambian laws and policies that address the game meat chain, focused on game meat zoonosis risks, and interviews with stakeholders in the game meat supply chain. This was followed by a zoonoses vulnerability assessment of the chain prompted by the absence of specific game meat regulations. The policy analysis revealed a lack of specific regulations governing game meat safety, with limited control over game meat along the supply chain. Several gaps in the law and policy frameworks were identified. To enhance game meat safety and reduce zoonotic disease transmission along the game meat supply chain, the use of a zoonotic control framework is recommended. We conclude with a discussion of the international implications of this Zambian use case.